STRATEGI PENGEMBANGAN POTENSI WISATA PANTAI ANYER PROVINSI BANTEN PADA MASA PANDEMI COVID-19 - Masduki; Jamaluddin; Ida Mursidah (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2020)
This study is a qualitative research which aims to describe the Strategy for theDevelopment of Tourism Potentials of Anyer Beach in Banten Province during the COVID-19Pandemic. The research was conducted in groups with a time frame from September to November2020 in the Anyer Beach Tourism Area, Banten Province. Researchers only used 23 objects asresearch samples consisting of hotel managers, tourist destinations, restaurants and others that areeasily accessible to researchers. The results of this study indicate that the Anyer beach tourism areawhich is located in Serang Regency, Banten Province is very potential if it is used as one of the halaltourism destinations. Several strategic efforts have been made to keep this industry in existenceduring a pandemic, including massiv promos via social media, continuing to implement healthprotocellers so that visitors are safe and comfortable and following the CHSE certification test(cleanliness, health, safety, environment) from the Ministry of Economic Tourism. Creative.